Identification Critical Success Factors of Geographic Information System Development in Indonesia with AHP Approach - Aini, Nur; Kurniawan, Wawan; Payani, Agnes Sondita; Go, Ratna Yulika (Society of Visual Informatics, 2024)
An Indonesian government agency in the field of research is developing a Geographic Information System (GIS) to distribute remote sensing data to customers. To prevent project failure, it is crucial to understand the success criteria related to project objectives and the critical success factors (CSFs), which drive project success. This research identifies these CSFs, enabling organizations to prioritize project success factors. The Analytic Hierarchy Process (AHP) ranks project success criteria and CSFs. The mixed research methodology incorporates qualitative elements through discussions with the project manager to validate the AHP hierarchy structure and quantitative aspects through questionnaires used to calculate weighted priorities using AHP. Results show stakeholder satisfaction and objective achievement as the top-ranked success criteria. The top 5 CSFs identified are team commitment and participation, clear roles and responsibilities, leadership, knowledge management, appropriate tools, infrastructure, and resources. Based on the success criteria ranking, development should enhance system functionality to maintain user satisfaction and achieve project objectives. Meanwhile, prioritizing human resources and providing adequate resources are crucial based on the identified top 5 CSFs, contributing to increased development success. This outcome aims to assist firms in improving project management and identifying the most critical success elements for GIS development. Furthermore, this research will likely be a learning experience for other government organizations seeking to enhance their information system development efforts.